Airline Seat Share: A Study in False Optimization - Barcun, Seymour D.; Jeming, Peter (Management Science, 1973)
An interactive model is developed which correctly predicts the problems faced by the airline industry today. The function of the model is to simulate the decision making process of determining the number of seats (and therefore planes) a competitor will fly in a given “market.” (A market is a city pair, e.g., the Washington-Chicago market.) This model of competition in a regulated industry considers the interaction of seat share, market share and profitability as major determinants of policy. Simulated data is presented for three cases in a two-competitor market. Case 1 supposes this model is used to determine policy only by one airline. Case 2 assumes the model is used by both competitors, but neither will fly a market if losses are encountered. Case 3 assumes that the model is used by both competitors, and losses will be taken to insure a favorable market share for future profitability.